AN ASSESSMENT OF NIGERIA’S PREPAREDNESS TO ENVIRONMENTAL DISASTERS FROM ITS COMMITMENT TO INTERNATIONAL ENVIRONMENTAL TREATIES - Al-Amin, Mohammed A. (European Scientific Journal, ESJ, 2013)
Environmental disasters are events that do not give notice to it’s occurrence but are tackled through careful planning and execution of contingency measures. The flood disaster of 2012 in Nigeria have revealed several challenges regarding the nations disaster preparedness, the need to strengthen Nigeria’s Disaster Risk Reduction (DRR) mechanism is therefore particularly timely. This paper was an attempt to review the Nigeria’s disaster preparedness through assessment of the country’s commitment to the international instruments of environmental management as contained in several treaties and agreements. The review has indicated a general trend of accepting such instrument through the country’s ratification of them, but with little efforts at it’s domestications and setting of the necessary structures for its implementation. The research found out that this administrative setback is hampering Nigeria from being fully prepared for eventualities of extreme environmental events; especially as occasioned by climate change. Many recommendations were made for institutional, policy and attitudinal adjustments to forestall calamities and quantum destructions resulting from environmental disasters.